Recent advances in sago (Metroxylon sagu) fibres, biopolymers, biocomposites, and their prospective applications in industry: a comprehensive review - AL-Fakih, Ghassan.O.A.; Ilyas, R.A.; M. Huzaifah, M.R.; El-Shafay, A.S. (Elsevier, 2024)
Escalating petroleum depletion and environmental crises linked to conventional plastics have fueled interest in eco-friendly alternatives. Natural fibres and biopolymers are garnering increasing attention due to their sustainability. The sago palm (Metroxylon sagu), a tropical tree, holds potential for such materials, with celluloserich fibres (42.4–44.12 %) showcasing strong mechanics. Extracted sago palm starch can be blended, reinforced, or plasticised for improved traits. However, a comprehensive review of sago palm fibres, starch, and biocomposites is notably absent. This paper fills this void, meticulously assessing recent advancements in sago palm fibre, cellulose and starch properties, and their eco-friendly composite fabrication. Moreover, it uncovers the latent prospects of sago palm fibres and biopolymers across industries like automotive, packaging, and bioenergy. This review presents a crucial resource for envisaging and realising sustainable materials.